Risk factors of acute myocardial infarction in elderly and nonelderly patients: a comparative retrospective study done in a rural tertiary care centre of India - Kamendu, Abhishek; Aslami, Ahmad Nadeem (International Journal of Advances in Medicine, 2018)
Background: Cardiovascular diseases are the most common diagnosis in the elderly, and the first cause of death in men and women over 60 years. It is not clear if the risk factors of acute myocardial infarction (AMI) are different in elderly and non-elderly people. The aim of this study was to compare the prevalence of risk factors of acute myocardial infarction between elderly and non-elderly patients who had been admitted to hospital for the first attack of acute myocardial infarction (AMI). Methods: A retrospective study was done in Narayan Medical College and Hospital, Jamuhar, Sasaram, Bihar from January 2017 to December 2017. Study population were all patients who were admitted due to AMI in medicine ward. Patients were selected as per World Health Organization guidelines. The patients were divided into two groups, non-elderly patients of <60 years and elderly patients of ≥60 years. Results: Among different risk factors, diabetes and hypertension were more common in elderly than their non-elderly counterparts, and male gender, smoking and family history of ischemic heart disease was more common in non-elderly patients than elderly ones. Conclusions: This study provide vital information on young AMI patients amongst the diverse population of north India and will help to guide the treating physicians and the health care system to adopt appropriate steps directed towards primary and secondary prevention of AMI in young patients of this region, especially smoking cessation, which is the commonest modifiable risk factor, in their most productive years of life.